2019
DOI: 10.1590/0100-6991e-20192154
|View full text |Cite
|
Sign up to set email alerts
|

O uso da tomografia computadorizada na triagem da lesão cardíaca penetrante.

Abstract: RESUMO Objetivo: determinar se a tomografia computadorizada representa uma opção segura para triagem de lesões cardíacas penetrantes. Métodos: estudo transversal retrospectivo, que confrontou os achados tomográficos com os detectados na exploração cirúrgica em pacientes operados por suspeita de trauma cardíaco no período de janeiro de 2016 a janeiro de 2018. Resultados: setenta e dois casos foram analisados; 97,2% eram do sexo masculino e a faixa etária mais prevalente foi de 20 a 29 anos; 56,9% apresentara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The main mechanism of PCI was SW with an incidence of 67%, which is in accordance with literature, that reports an incidence from 43 to 74%. (Jones et al, 2014;Kaljusto et al, 2015;Stranch, Zarzaur and Savage, 2017;Góes Junior et al, 2019) However, different authors have reported an increase of GSW over SW, which could be best explained for the easy access to guns in different countries. (Campbell et al, 1997;Asensio et al, 2009;Seamon et al, 2015;Morse et al, 2016) Ventricles were compromised on 67% of the cases, and that may be best explained for its size.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main mechanism of PCI was SW with an incidence of 67%, which is in accordance with literature, that reports an incidence from 43 to 74%. (Jones et al, 2014;Kaljusto et al, 2015;Stranch, Zarzaur and Savage, 2017;Góes Junior et al, 2019) However, different authors have reported an increase of GSW over SW, which could be best explained for the easy access to guns in different countries. (Campbell et al, 1997;Asensio et al, 2009;Seamon et al, 2015;Morse et al, 2016) Ventricles were compromised on 67% of the cases, and that may be best explained for its size.…”
Section: Discussionmentioning
confidence: 99%
“…They remain the most affected chambers of the heart, around 60-70% (Thorson et al, 2012;Besir, Gokalp and Eygi, 2015;Kaljusto et al, 2015;Seamon et al, 2015). However, the right ventricle is the most affected chamber (Topal, Celik and Eren, 2010;Thorson et al, 2012;Morse et al, 2016;Góes Junior et al, 2019); this can be explained due to the anatomical disposition, as the right ventricle lies just posterior to the sternum, and it is more approachable to SW. (Kang et al, 2009)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations